Using Facebook for health-related research study recruitment and program delivery. (June 2016) - Pedersen, Eric R; Kurz, Jeremy
Highlights: There is much potential for use of Facebook in health-related research and program delivery. We review studies that have used Facebook to recruit diverse samples and deliver programs. Facebook studies have generally reported success with recruitment. Recommendations for researchers interested in using Facebook are discussed. Abstract : Facebook has become an important tool for recruiting research participants and for program delivery. Given the wide use of Facebook, there is much potential for the site to help with recruitment efforts in both physical and behavioral health care arenas; reaching groups typically difficult to recruit and providing outreach to individuals that may not have received services elsewhere. Health studies using Facebook have generally reported success, including cost-effectiveness, recruitment of samples in brief periods of time, and ability to locate participants for follow-up research. Still, the use of Facebook for research and program delivery is a relatively new area that warrants more research attention and guidance around issues like validity of data, representativeness of samples, and protections of human subjects.